Colorless Tsukuru Tazaki and his years of pilgrimage : a novel - Murakami, Haruki, 1949-; Gabriel, Philip, 1953- (New York : Alfred A. Knopf, 2014)
'The new novel--a book that sold more than a million copies the first week it went on sale in Japan--from the internationally acclaimed author, his first since IQ84'--
Keywords: FICTION / Literary; FICTION / Coming of Age; FICTION / Fantasy / Contemporary